One-pot bottom-up fabrication of biocompatible PEGylated WS 2 nanoparticles for CT-guided photothermal therapy of tumors in vivo - Wang, Jiang-Tao; Zhang, Wei; Wang, Wan-Bi; Wu, Yong-Juan; Zhou, Ling; Cao, Feng (Biochemical and biophysical research communications, 2019)
Tungsten disulfide (WS ), which enjoyed a good potential to be a promising clinical theranostic agent for cancer treatment, is still subject to the tedious synthesis procedure. Here, we reported a one-pot 'bottom-up' hydrothermal strategy for the fabrication of PEGylated WS nanoparticles (NPs). The WS -PEG nanoparticles were characterized systematically. The CT imaging and photothermal therapy against tumor as well as biosafety in vitro and in vivo were also investigated. The obtained WS -PEG NPs enjoyed obvious merits of good solubility and favorable photothermal performance. WS -PEG NPs exhibited desirable photothermal ablation ability against cancer cells and cancer cell-bearing mice in vitro and in vivo. MTT assay and histological analysis demonstrated the low cytotoxicity and biotoxicity of WS -PEG NPs, providing a valid biosafety guarantee for the coming biomedical applications. In addition, thanks to the obvious X-ray attenuation of W atom, the WS -PEG NPs can also be served as a favorable contrast agent for CT imaging of tumors. WS -PEG NPs has enjoyed a good potential to be a promising clinical CT-guided photothermal therapeutic agent against cancers.